Uterine rupture after previous low segment transverse cesarean is rarely catastrophic. (19th March 2018) - Soltsman, Sofia; Perlitz, Yuri; Ben Ami, Moshe; Ben Shlomo, Izhar
Abstract: Objective: The cornerstone of concerns over trial of labor after cesarean (TOLAC) is the risk of uterine rupture. The purpose of this study was to document the rate of uterine rupture during TOLAC and to delineate its severity and consequences. Materials and methods: We retrospectively collected the data on vaginal and cesarean deliveries after a previous cesarean section with specific emphasis on uterine rupture and dehiscence in our center from 2006 through 2013. Results: 22, 670 deliveries were registered, with 18.2% rate of cesarean section. 2890 women had a single cesarean scar; of them 1206 delivered vaginally and 194 were re-operated during unsuccessful TOLAC. Seven cases of uterine rupture and 16 cases of dehiscence were recorded. There were no maternal, intrapartum or neonatal deaths, and no cesarean hysterectomy. There was one re-laparotomy, one ICU admission, and one blood transfusion; one neonate was admitted to NICU. TOLAC was successful in 86.1% of cases. Conclusions: Cautious selection and close monitoring of candidates are the cornerstones of successful management of TOLAC. Readily available facilities for emergency cesarean delivery and concerted obstetrical team can save the mother and child from catastrophic complications.